Providence : the story of a fifty-year vision quest - Quinn, Daniel (New York : Bantam Books, 1995)
"Providence is the record of Daniel Quinn's fascinating fifty-year voyage to a revolutionary way of seeing the world. Quinn's journey takes him from a prophetic midnight childhood dream in an Omaha boardinghouse, to a mysterious encounter in the hills of Kentucky as a young Trappist monk, to disenchantment with existing forms of organized religion, and finally to his personal rediscovery of humankind's first and only universal religion, one that is now all but forgotten. Along the way, Quinn expands on the ideas put forth in Ishmael and explores their meaning in daily life."-
Keywords: Quinn, Daniel; Quinn, Daniel -- Religion; Trappists -- United States -- Biography; Novelists, American -- 20th century -- Biography; Spiritual life